Integrated metabolomics and proteomics revealed astragaloside IV inhibiting Pdxk-mediated vitamin B6 metabolism based on liquid chromatography-tandem mass spectrometry combined with pattern recognition and correlation analysis - Shi Qiu; Sifan Guo; Zhibo Wang; Ying Cai; Dandan Xie; Wanying Sun; Aihua Zhang (Journal of Functional Foods)
Metabolic abnormalities lead to the dysfunction of metabolic pathways and metabolite accumulation or deficiency which is well-recognized hallmarks of diseases. Unique metabolic needs of cells highlight the potential for fruitful drug and target discovery. Astragaloside IV (ASIV) is a representative component of traditional herbs Astragalus membranaceus which belongs to medicinal food homology, but the molecular targets regulating cellular amino acid (AA) metabolism of the therapeutic effect are still unclear. Here, we integrated metabolomics and proteomics approach with pattern recognition to exploring potential targets and AA metabolic characteristics of ASIV on diabetic db/db mouse and Min6 cell lines. Intracellular metabolites and the dysregulated proteins were detected and analyzed by liquid chromatography/mass spectrometry/mass spectrometry and parallel reaction monitoring assays. According to the correlation matrix of the dysregulated metabolites/proteins interactions, we found that Pdxk was ranked as top target signature that was closely related to AA metabolism. Mechanistically, ASIV inhibits Pdxk by suppression of the vitamin B6 pathway, thereby ameliorating AA metabolism disorders. Intriguingly, ASIV affected the metabolite production of the vitamin B6 metabolism, especially had a significantly downregulated expression of 4-pyridoxic acid and pyridoxal 5′-phosphate, leading to the suppression of AA metabolism pathway. It also provides evidence that integrated metabolomics and proteomics approach reveal ASIV inhibits Pdxk as a potential therapeutic target by regulating AA metabolic homeostasis for diabetes treatment, and laying a new paradigm for diabetes treatment. In short, the integrated metabolomics and proteomics approach could reveal ASIV inhibits Pdxk as a potential target by regulating AA metabolic homeostasis and laying a new paradigm for precision treatment of future diseases.